Palliative opioid use, palliative sedation and euthanasia: reaffirming the distinction. Issue 1 (20th June 2019) - Schofield, Guy; Baker, Idris; Bullock, Rachel; Clare, Hannah; Clark, Paul; Willis, Derek; Gannon, Craig; George, Rob
Abstract : We read with interest the extended essay published from Riisfeldt and are encouraged by an empirical ethics article which attempts to ground theory and its claims in the real world. However, such attempts also have real-world consequences. We are concerned to read the paper's conclusion that clinical evidence weakens the distinction between euthanasia and normal palliative care prescribing. This is important. Globally, the most significant barrier to adequate symptom control in people with life-limiting illness is poor access to opioid analgesia. Opiophobia makes clinicians reluctant to prescribe and their patients reluctant to take opioids that might provide significant improvements in quality of life. We argue that the evidence base for the safety of opioid prescribing is broader than that presented, restricting the search to palliative care literature produces significant bias as safety experience and literature for opioids and sedatives exists in many fields. This is not acknowledged in the synthesis presented. By considering additional evidence, we reject the need for agnosticism and reaffirm that palliative opioid prescribing is safe. Second, palliative sedation in a clinical context is a poorly defined concept covering multiple interventions and treatment intentions. We detail these and show that continuous deep palliative sedation (CDPS) is a specific practice that remains controversial globally and is not considered routine practice. Rejecting agnosticism towards opioids and excluding CDPS from the definition of routine care allows the rejection of Riisfeldt's headline conclusion. On these grounds, we reaffirm the important distinction between palliative care prescribing and euthanasia in practice.